2019
DOI: 10.1039/c8ew00790j
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation pathways of the herbicide bentazone in filter sand used for drinking water treatment

Abstract: Three bentazone biodegradation pathways were identified in rapid sand filter material and relevant transformation products were less hazardous than bentazone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Our previous work has shown how a methanotrophic enrichment culture co-metabolically transformed bentazone to 6-OH-, 8-OH-, isopropyl-OH-, and di-OH-bentazone which accumulated in this enrichment culture (Hedegaard et al, 2018). However, these hydroxylated transformation products could not be detected during bentazone degradation in filter material from a waterworks, whereas the presence of further degraded transformation products demonstrated the importance of other metabolic pathways in these systems (Hedegaard et al, 2019). Thus, it is still unknown whether the initial bentazone degradation step in filter material depends on methane oxidation or other biological processes and to what extent this is valid in water treatment system.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our previous work has shown how a methanotrophic enrichment culture co-metabolically transformed bentazone to 6-OH-, 8-OH-, isopropyl-OH-, and di-OH-bentazone which accumulated in this enrichment culture (Hedegaard et al, 2018). However, these hydroxylated transformation products could not be detected during bentazone degradation in filter material from a waterworks, whereas the presence of further degraded transformation products demonstrated the importance of other metabolic pathways in these systems (Hedegaard et al, 2019). Thus, it is still unknown whether the initial bentazone degradation step in filter material depends on methane oxidation or other biological processes and to what extent this is valid in water treatment system.…”
Section: Introductionmentioning
confidence: 79%
“…In both approaches, bentazone removal in the filter material from Sjaelsø Plant II and Stenholt was much larger than in filter material from the remaining waterworks (Supplementary Figure S1). However, even though degradation clearly followed a linear trend through the entire period when measured by HPLC (Supplementary Figure S1A), the dissolved 14 C-activity did not decrease substantially after 1 day at Sjaelsø Plant II, or after 7 days at Stenholt waterworks (Supplementary Figure S1B), probably due to formation of transformation products (Hedegaard et al, 2019).…”
Section: Methane In the Raw Water And Removal Of Bentazone In Filter Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, Hedegaard et al, and (2019) showed that 92% of bentazone, a widely used herbicide and often a recalcitrant groundwater contaminant, was degraded within 13 days in RSF. Moreover, Hedegaard et al (2019) suggested that various microbial groups were involved in the biodegradation: methanotrophs transformed bentazone to various hydroxylated TPs; thereafter, a diverse community was involved in the full degradation of TPs.…”
Section: Evaluation and Discussion On Omps Removal In Existing Rsf Symentioning
confidence: 98%
“…Biodegradation of bentazone in biological rapid sand filtration occurred mainly through three main biotransformation pathways: oxidation of the isopropyl moiety to the corresponding carboxylic acid, oxidation of the aromatic ring leading to ring cleavage and subsequent decarboxylation, and N-methylation followed by oxidation to a carboxylic acid [25].…”
Section: Introductionmentioning
confidence: 99%